An exploratory study of the Work Ability Index (WAI) and its components in a group of computer workers. - Nunes, Isabel L.; Costa, Ana Filipa; Puga-Leal, Rogério (Work, 2011)
Objective: The objective of this paper is to present a study on the assessment of the work ability of a group of aged computers workers. The study was developed with the goal of creating a decision making framework oriented towards the maintenance of the health and working ability of aged workers. Participants: Fifty computer workers participated in this study. They were administrative secretaries and computer technicians working mainly with office computers. Methods: The method used to assess the work ability was the Work Ability Index (WAI). Results: 78% of the participants had good or excellent work ability and only 2% a poor one. The average WAI score was 40.5 (SD=5.761; min=27; max=49). This study confirms the decrease in work ability of workers while aging. The group overall work ability was slightly higher than the reference values develop by the Finnish Institute of Occupational Health. Conclusions: The assessment of work ability is fundamental to make age-friendly workplaces. WAI is one tool designed to perform such assessment. The results obtained could assist the early identification of situations where employees are struggling with their work ability, thus helping to prioritize ergonomic interventions devoted to improve the working conditions, and allowing the continued employment of aging workers on their current job.